Characterization of a novel mosquitocidal toxin of Cry50Ba and its potential synergism with other mosquitocidal toxins. (November 2017) - Zhang, Wenfei; Yu, Silan; Peng, Silun; Gong, Jianru; Qian, Jiangzhao; He, Jianqiao; Dai, Wenyu; Wang, Ruiping
Abstract: A putative toxin gene of cry50Ba was successfully expressed in E. coli cells and confirmed that the purified Cry50Ba toxin had very high toxic activity against Culex quinquefasciatus larvae. Furthermore, the potential synergism of Cry50Ba toxin with Cry2Aa, Cry4Aa and Cry11Aa at a ratio of 1:1 was investigated. Although no significant synergism with other toxins was observed, the Cry50Ba as a novel toxin could be used to delay rapid onset of resistance in mosquito. Graphical abstract: Highlights: The cry50Ba gene was successfully expressed in E. coli cells. The potential synergism of Cry50Ba with other toxins was investigated. The purified Cry50Ba toxin had very high toxic activity against Culex quinquefasciatus larvae. Cry50Ba protein is an effective protein with potential use to delay resistance development in mosquitoes.